Peningkatan Kemampuan Literasi Matematika Siswa dengan Penerapan Realistic Mathematics Education Ditinjau dari Adversity Quotient - Shafna Armiyah Gultom; Budi Halomoan Siregar (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine the improvement of students' mathematical literacy skills through the application of the Realistic Mathematics Education (RME) approach compared to Teacher Centered Learning (TCL), and to analyze the interaction between the learning approaches and students' Adversity Quotient (AQ) levels. The method used was a quasi-experiment with subjects of grade VIII students at SMP IT Nurul Fadhilah Percut Sei Tuan. The research instruments included an Adversity Response Profile (ARP) questionnaire and a mathematical literacy test. The results showed an increase in mathematical literacy skills in students who learned using the RME approach, with an N-gain of 0.589 higher than the class using TCL. This study also found an interaction between the learning approach and AQ levels on students' mathematical literacy skills. Students in the climbers category showed better resilience and ability in solving mathematical problems than students categorized as campers or quitters. This finding confirms that the application of contextual learning such as RME with strengthening non-cognitive aspects such as AQ, has an important role in improving students' mathematical literacy.